Afforestation Technique for Eroded Areas in Damodar Catchment - Goswami, P. C. (Indian Forester, 1957)
Afforestation of highly eroded areas in the upper Damodar Catchment, Bihar, has been taken up only recently. The Soil Conservation Department of the Damodar Valley Corporation started afforestation work in 1952 and now follows a programme of 1,000 acres annually. The paper describes the technique followed. Topography, climate and soil of the region is described. Areas for afforestation are selected generally on the basis of land capability and are fenced with barbed wire. Gullies are treated by diverting water from the heads and putting check-dams. The greater parts of the areas are transplanted with seedlings, 2 feet or more in height, in specially prepared pits to establish plantations quickly. Sowing is done only on selected locations using species that do well by direct sowing. Contour trenching in most areas is found unnecessary as run-off and sheet erosion is largely controlled by heavy grass growth resulting from closure and fire control. Contour trenching has not been found effective in increasing growth and is done only in areas where vegetative measures alone are not sufficient. Species used are listed. Sal has been raised successfully by direct sowing in 1956 and more extensive trial will continue. Need for further trial and observation on methods of soil preparation, species to be used, economics of the plantations, etc., are stressed.